Metabolic effects of RUBCN/Rubicon deficiency in kidney proximal tubular epithelial cells. Issue 10 (2nd October 2020) - Matsuda, Jun; Takahashi, Atsushi; Takabatake, Yoshitsugu; Sakai, Shinsuke; Minami, Satoshi; Yamamoto, Takeshi; Fujimura, Ryuta; Namba-Hamano, Tomoko; Yonishi, Hiroaki; Nakamura, Jun; Kimura, Tomonori; Kaimori, Jun-Ya; et al.
ABSTRACT: Macroautophagy/autophagy is a lysosomal degradation system which plays a protective role against kidney injury. RUBCN/Rubicon (RUN domain and cysteine-rich domain containing, Beclin 1-interacting protein) inhibits the fusion of autophagosomes and lysosomes. However, its physiological role in kidney proximal tubular epithelial cells (PTECs) remains uncertain. In the current study, we analyzed the phenotype of newly generated PTEC-specific rubcn -deficient (KO) mice. Additionally, we investigated the role of RUBCN in lipid metabolism using isolated rubcn -deficient PTECs. Although KO mice exhibited sustained high autophagic flux in PTECs, they were not protected from acute ischemic kidney injury. Unexpectedly, KO mice exhibited hallmark features of metabolic syndrome accompanied by expanded lysosomes containing multi-layered phospholipids in PTECs. RUBCN deficiency in cultured PTECs promoted the mobilization of phospholipids from cellular membranes to lysosomes via enhanced autophagy. Treatment of KO PTECs with oleic acid accelerated fatty acids transfer to mitochondria. Furthermore, KO PTECs promoted massive triglyceride accumulation in hepatocytes (BNL-CL2 cells) co-cultured in transwell, suggesting accelerated fatty acids efflux from the PTECs contributes to the metabolic syndrome in KO mice. This study shows that sustained high autophagic flux by RUBCN deficiency in PTECs leads to metabolic syndrome concomitantly with an accelerated mobilization of phospholipids from cellular membranes to lysosomes. Abbreviations : ABC: ATP binding cassette; ACADM: acyl-CoA dehydrogenase medium chain; ACTB: actin, beta; ATG: autophagy related; AUC: area under the curve; Baf: bafilomycin A1 ; BAT: brown adipose tissue; BODIPY: boron-dipyrromethene; BSA: bovine serum albumin; BW: body weight; CAT: chloramphenicol acetyltransferase; CM: complete medium; CPT1A: carnitine palmitoyltransferase 1a, liver; CQ: chloroquine; CTRL: control; EGFP: enhanced green fluorescent protein; CTSD: cathepsin D; EAT: epididymal adipose tissue; EGFR: epidermal growth factor receptor; EIF4EBP1: eukaryotic translation initiation factor 4E binding protein 1; FA: fatty acid; FBS: fetal bovine serum; GTT: glucose tolerance test; HE: hematoxylin and eosin; HFD: high-fat diet; I/R: ischemia-reperfusion; ITT: insulin tolerance test; KAP: kidney androgen regulated protein; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LD: lipid droplet; LRP2: low density lipoprotein receptor related protein 2; MAP1LC3B: microtubule associated protein 1 light chain 3 beta; MAT: mesenteric adipose tissue; MS: mass spectrometry; MTOR: mechanistic target of rapamycin kinase; MTORC1: MTOR complex 1; NDRG1: N-myc downstream regulated 1; NDUFB5: NADH:ubiquinone oxidoreductase subunit B5; NEFA: non-esterified fatty acid; OA: oleic acid; OCT: optimal cutting temperature; ORO: Oil Red O; PAS: Periodic-acid Schiff; PFA: paraformaldehyde; PIK3C3: phosphatidylinositol 3-kinase catalytic subunit type 3; PPARA: peroxisome proliferator activated receptor alpha; PPARGC1A: PPARG coactivator 1 alpha; PTEC: proximal tubular epithelial cell; RAB7A: RAB7A, member RAS oncogene family; RPS6: ribosomal protein S6; RPS6KB1: ribosomal protein S6 kinase B1; RT: reverse transcription; RUBCN: rubicon autophagy regulator; SAT: subcutaneous adipose tissue; SFC: supercritical ﬂuid chromatography; SQSTM1: sequestosome 1; SREBF1: sterol regulatory element binding transcription factor 1; SV-40: simian virus-40; TFEB: transcription factor EB; TG: triglyceride; TS: tissue specific; TUNEL: terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling; UN: urea nitrogen; UQCRB: ubiquinol-cytochrome c reductase binding protein; UVRAG: UV radiation resistance associated; VPS: vacuolar protein sorting; WAT: white adipose tissue.